HISTORICAL AND CONTEMPORARY DEVELOPMENTS IN THE EDUCATION SYSTEMS OF ENGLAND, WALES, SCOTLAND, AND NORTHERN IRELAND - Abdurakhmanov Turakhon Saydullayevich; Mominjonova Rahimaxon (TADQIQOTLAR, 2025)
Abstract:This  article  explores  the  evolution  of  the  education  systems  in England,  Wales,  Scotland,  and  Northern  Ireland  from  their  historical  roots  to  the modern-day structures. It highlights the unique characteristics of each region’s system, influenced by their political autonomy and cultural identity. The article also discusses recent changes in curricula, assessments, governance, and technology integration in schools, and analyses how these reforms aim to improve equity, quality, and inclusivity across the United Kingdom.